Inpatient or outpatient total elbow arthroplasty: a comparison of patient populations and 30-day surgical outcomes from the American College of Surgeons National Surgical Quality Improvement Program - David Momtaz; Farhan Ahmad; Aaron Singh; Emilie Song; Dean Slocum; Abdullah Ghali; Adham Abdelfattah (Clinics in Shoulder and Elbow, 2023)
Background Total elbow arthroplasty (TEA) is uncommon, but growing in incidence. Traditionally an inpatient operation, a growing number are performed outpatient, consistent with general trends in orthopedic surgery. The aim of this study was to compare TEA outcomes between inpatient and outpatient surgical settings. Secondarily, we sought to identify patient characteristics that predict the operative setting. Methods Patient data were collected from the American College of Surgeons National Quality Improvement Program. Preoperative variables, including patient demographics and comorbidities, were recorded, and baseline differences were assessed via multivariate regression to predict operative setting. Multivariate regression was also used to compare postoperative complications within 30 days. Results A total of 468 patients, 303 inpatient and 165 outpatient procedures, were identified for inclusion. Hypoalbuminemia (odds ratio [OR], 2.5; P=0.029), history of chronic obstructive pulmonary disorder or pneumonia (OR, 2.4; P=0.029), and diabetes mellitus (OR, 2.5; P=0.001) were significantly associated with inpatient TEA, as were greater odds of any complication (OR, 4.1; P<0.001) or adverse discharge (OR, 4.5; P<0.001) and decreased odds of reoperation (OR, 0.4; P=0.037). Conclusions Patients undergoing inpatient TEA are generally more comorbid, and inpatient surgery is associated with greater odds of complications and adverse discharge. However, we found higher rates of reoperation in outpatient TEA. Our findings suggest outpatient TEA is safe, although patients with a higher comorbidity burden may require inpatient surgery. Level of evidence III